Evaluation of post-pandemic immigration services at Immigration Office Class I Non-checkpoint Pati - Fitriyono, Junaidul (Publisia: Jurnal Ilmu Administrasi Publik, 2024)
Immigration services are one of the services affected by the COVID-19 pandemic. However, as the handling got better, the vaccination program became more widespread and the spread became lower, the Government began to provide some leeway including the opening of borders. People who want to travel between countries begin to prepare themselves by applying for a passport. Immigration Office Class I Non-Checkpoint Pati as an Immigration Technical Implementation Unit faces fluctuations in applications for passport issuance during this pandemic. This is descriptive qualitative research using literature review method, where data were gained from several sources such as related articles, journals, news and data which is released by government. The data were collected during period of time December 2021 until May 2022. From the analysis, it is obtained that issues and information, as well as announcements from the government, influence people to apply for passports. Improving passport services must also consider service quality. It can be described from Internal surveys and also Google Review. There was dynamic condition from the period of time of the analysis which showed dominant positive responses for the services to Immigration Office Pati from immigration service user community.